Lean Principles in Small-Medium Enterprises in Malaysia: Creating A Web-Based Training - Karrim Wani1, Zarirah; Wei, Yap Woan; Ab Samat, Hasnida; Abdullah, Ahmad Baharuddin (Journal of Advanced Industrial Technology and Application, 2023)
Lean principles (LP) are established strategies to increase the throughput of business organizations. Many large companies have benefited from the implementations of LP in their organizations. However, the acceptance of LP implementations among Small and Medium Enterprises (SMEs) remained low, primarily due to continued prejudice and lack of accessibility to the LP tools. This paper presents a Web-based Training (WBT) approach to alleviate such constraints and to accommodate the circumstances of SMEs in term of their financial, time and knowledge resources. In the first part of this paper, the fundamental concepts of LP, SME, and WBT are presented based on the review of literature studies. Subsequently, the development of the optimal modules for WBT, based on survey validations on the connectivity of LP and SMEs in Malaysia, is elaborated, highlighting the use of simple words and terms for ease of comprehension of the targeted SME users.